2013
DOI: 10.1371/journal.pone.0068097
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Streptococcus pneumoniae from Different Types of Nasopharyngeal Swabs in Children

Abstract: BackgroundA better understanding of the epidemiology of nasopharyngeal carriage of Streptococcus pneumoniae is important to assess the impact of vaccination and the pathogenesis of pneumococcal disease. We compared the recovery of S. pneumoniae from nylon flocked, Dacron and rayon swabs.MethodsThe recovery of S. pneumoniae from mocked specimens using flocked, Dacron and rayon swabs were compared by culture. The yield from paired nasopharyngeal (NP) samples obtained from healthy children sampled with flocked an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…17 Finally, a flocked nylon fiber tip was used for the sampling because previous studies have shown that this ensures the highest rate of detection of S. pneumoniae, particularly in comparison with the more widely used Dacron and rayon swabs. 20 We did not observe differences in cycle threshold values comparing pneumococcal colonization in vaccinated and unvaccinated children, although it may be technically challenging to compare density of carriage using bacteria recovered on a small nylon tip as the size of the tip may be a limiting factor in assessing the magnitude of colonization.…”
Section: Discussionmentioning
confidence: 66%
“…17 Finally, a flocked nylon fiber tip was used for the sampling because previous studies have shown that this ensures the highest rate of detection of S. pneumoniae, particularly in comparison with the more widely used Dacron and rayon swabs. 20 We did not observe differences in cycle threshold values comparing pneumococcal colonization in vaccinated and unvaccinated children, although it may be technically challenging to compare density of carriage using bacteria recovered on a small nylon tip as the size of the tip may be a limiting factor in assessing the magnitude of colonization.…”
Section: Discussionmentioning
confidence: 66%
“…Oropharyngeal sampling was used to collect the pharyngeal secretions; it has recently been shown that it is a significantly better means of detecting the colonization by S. pneumoniae in adolescents, and young adults than the nasopharyngeal sampling used in the previous studies of younger children [13,15,16]. Finally, a flocked nylon fiber tip was used for sampling because previous studies have shown that this ensures the highest rate of detection of S. pneumoniae, particularly when compared with the more widely used Dacron and rayon swabs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Flocked nasopharyngeal swabs provide a similar yield to aspirates, are simpler to obtain than aspirates, 77 78 and may provide a better yield than other swab types. [79][80][81] Studies are inconsistent regarding the relative yield of nasopharyngeal versus oropharyngeal specimens for the detection of viruses; there may be incremental yield from testing of both specimen types for specific viruses such as influenza A or adenovirus. [82][83][84][85] Nasopharyngeal specimens may also be useful for the diagnosis of tuberculosis using the polymerase chain reaction (PCR) in children from whom it is not possible to obtain more representative lower respiratory tract samples.…”
Section: Respiratory Samplesmentioning
confidence: 99%